2018
DOI: 10.3390/ijms19041131
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Isocitrate Dehydrogenase 2 from Acinetobacter baumannii (AbIDH2) Reveals a Novel Dimeric Structure with Two Monomeric-IDH-Like Subunits

Abstract: Monomeric isocitrate dehydrogenases (IDHs) have a single polypeptide sizing around 85 kDa. The IDH2 from the opportunistic bacterium Acinetobacter baumannii (AbIDH2) with a mass of 83 kDa was formerly recognized as a typical monomeric IDH. However, both size exclusion chromatography and analytical ultracentrifugation analysis indicated that AbIDH2 exists as a homodimer in solution. The crystallographic study of the substrate/coenzyme-free AbIDH2 gave a dimeric structure and each subunit contained a domain I an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
(49 reference statements)
0
10
0
Order By: Relevance
“…Additionally, the K m values of PtIDH2 for NADP + were 37.37 ± 4.02 μM with Mn 2+ and 18.37 ± 2.94 μM with Mg 2+ , and the corresponding catalytic efficiency ( k cat / K m ) values were 3.22 and 2.36 μM −1 s −1 ( Supplementary Figure S2 ). These k cat / K m values were similar to those for the bacterial monomeric NADP-IDHs from Xanthomonas campestris (6.0 μM −1 s −1 with Mn 2+ ) and Streptomyces avermitilis (11.7 μM −1 s −1 with Mn 2+ ) ( Wang et al, 2011 ; Lv et al, 2016 ), but higher than those for the homodimeric NADP-IDH (contains two monomeric IDH-like subunits) from A. baumannii (0.39 μM −1 s −1 with Mn 2+ ) ( Wang et al, 2018 ) and lower than those for the monomeric IDHs from A. vinelandii (15.0 μM −1 s −1 with Mn 2+ ) and Xylella fastidiosa (96.5 μM −1 s −1 with Mn 2+ ) ( Watanabe et al, 2005 ; Lv et al, 2018 ).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Additionally, the K m values of PtIDH2 for NADP + were 37.37 ± 4.02 μM with Mn 2+ and 18.37 ± 2.94 μM with Mg 2+ , and the corresponding catalytic efficiency ( k cat / K m ) values were 3.22 and 2.36 μM −1 s −1 ( Supplementary Figure S2 ). These k cat / K m values were similar to those for the bacterial monomeric NADP-IDHs from Xanthomonas campestris (6.0 μM −1 s −1 with Mn 2+ ) and Streptomyces avermitilis (11.7 μM −1 s −1 with Mn 2+ ) ( Wang et al, 2011 ; Lv et al, 2016 ), but higher than those for the homodimeric NADP-IDH (contains two monomeric IDH-like subunits) from A. baumannii (0.39 μM −1 s −1 with Mn 2+ ) ( Wang et al, 2018 ) and lower than those for the monomeric IDHs from A. vinelandii (15.0 μM −1 s −1 with Mn 2+ ) and Xylella fastidiosa (96.5 μM −1 s −1 with Mn 2+ ) ( Watanabe et al, 2005 ; Lv et al, 2018 ).…”
Section: Resultsmentioning
confidence: 61%
“…Based on phylogeny, the IDH protein family has been classified into three subfamilies, namely, types I, II, and III. Additionally, two types of IDHs—monomeric and homodimeric NADP-IDHs—can be distinguished in the type III subfamily based on coenzyme specificity and oligomeric state ( Wang et al, 2015 ; Wang et al, 2018 ). All type III IDHs reported to date are derived from prokaryotes, including both bacteria and archaea ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IDHs are widely distributed in living organisms, including bacteria, archaea, and eukaryotes. A phylogenetic analysis revealed that the IDH protein family can be divided into three subfamilies: type I, type II, and type III [ 10 , 11 ]. All archaeal and the vast majority of bacterial homodimeric NAD(P)-IDHs and eukaryotic hetero oligomeric NAD-IDHs are grouped together in the type I subfamily.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the type I and II IDHs with 400-amino acid polypeptide chains, the bacterial monomeric NAD(P)-IDHs belonged to the type III subfamily, the polypeptide chains of which are approximate 740-amino acid in length. We demonstrated in a previous study that some monomeric IDHs exist as dimers in solution, thus expanding the diversity of the IDH family [ 10 ].…”
Section: Introductionmentioning
confidence: 99%